Berczeli Anzelm Károlyhoz - Tevan Nyomda és Kiadó (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1933)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek